The utilization of m-smart fisherman as media of fisherman information in South Kalimantan, Indonesia - ., Atika; Puspita Dewi, Ira (International Journal of Engineering and Technology, 2019)
M-Smart Fisherman is a mobile service, which one of its functions is as a mobile internet media for fishermen in accessing information. This research reveals how the utilization of M-Smart Fisherman Service as information media for fisherman in South Kalimantan. The research using a qualitative approach. The process of data collection is done by using in-depth interview and Focus Group Discussion. The results revealed that the m-Fisherman Smart car until now only functioned as a means of administrative services of fishermen, while the function as a mobile internet media for information facilities cannot be run.Â Â